Hemoglobin Expression in Nonerythroid Cells: Novel or Ubiquitous?. (5th November 2014) - Saha, Debarchana; Patgaonkar, Mandar; Shroff, Ankit; Ayyar, Kanchana; Bashir, Tahir; Reddy, K. V. R.
Abstract : Hemoglobin (Hb) is a major protein involved in transport of oxygen (O2 ). Red blood cells (RBCs) contain maximum amount of Hb and because of their unique structure and plasticity they transport O2 to various tissues of the body at an optimal concentration. Recently, it has been reported that, apart from RBCs, Hb is also expressed by nonerythroid cells such as epithelial cells of different origin. The cells expressing Hb are from the tissues where maintenance of O2 homeostasis is of paramount importance. Hb expression has been observed in the epithelial cells from human tissues including lungs, neurons, retina, and endometrium. Our group has recently demonstrated that Hb is expressed by the cervicovaginal epithelial cells. We further showed that, apart from maintaining O2 homeostasis, Hb and the peptides derived from it play an indispensable role in the protection of vaginal epithelium by exhibiting antimicrobial activity. In this review, we discuss the significance of Hb expression in vaginal epithelial cells and its role in the recognition of pathogens thereby reducing the risk and/or severity of inflammation and/or infections and the possible mechanism by which Hb exhibits antimicrobial and antioxidative functions.